Entrepreneurship and Security Solution toward Millennium Development Goals: Assessing the Effect of Entrepreneurial Education on Secondary School Students’ Ability to Address Economic Security Challenges in Anambra State, Nigeria - Uchenna Favour Muogbo; Uju Susan Muogbo; Chinwe Juliana Enemuo (Journal of Gender and Millennium Development Studies, 2025)
Background: This study examined the effect of entrepreneurial education on secondary school students' ability to address economic security challenges in Anambra State, Nigeria. Objective: The study aimed to investigate how entrepreneurial education influences students' critical thinking, innovation, and problem-solving skills, as well as its potential to enhance their ability to cope with economic instability. Method: Using a descriptive survey design, data were collected from all 263 principals across six educational zones. No sampling was done as the population was manageable. A self-structured 30-item questionnaire titled "Entrepreneurship Education and Students' Ability to Address Economic Security Challenges" (EEAASC) was used, with a reliability coefficient of 0.85 (Cronbach's Alpha). Data were analyzed using mean, standard deviation, and Chi-square tests. Results: Entrepreneurial education significantly enhanced students' critical thinking, innovation, and problem-solving abilities. It also improved their awareness of self-reliant economic skills and their capacity to cope with economic instability in Anambra State and Nigeria as a whole. Conclusion; Entrepreneurial education plays a crucial role in empowering students to address economic security challenges. It fosters key skills necessary for coping with economic instability and enhancing self-reliance. Recommendation: recommendations were made to integrate entrepreneurial education into the curriculum, equipping students with the skills necessary to tackle economic challenges effectively.